Synthesis and anticancer activities of ageladine A and structural analogs - Ma, Yuelong (2009)
A series of ageladine A analogs that include 2-aminoimidazo[4,5-c]azepines (seven-membered rings) and 2-amino-3H-imidazo[4,5-c]pyridine (six-membered rings) derivatives were synthesized and evaluated for their anticancer effects against several human cancer cell lines and MMP-2 inhibition in vitro. Only compounds possessing the aromatic azepine (seven-membered ring) core showed anticancer activity with IC(50) values in the low micromolar range.